PENERAPAN PEMANFAATAN TEKNOLOGI DITINJAU DARI TEORI KEPRIBADIAN MORAL - Yohanes Probo Dwi (Psibernetika, 2017)
Growth and technological development, and the advancement of human life, evolved very significantly. The existence of technology and human existence now, as if like two sides of a coin that can not be separated. Both are present and are complementary to one another. The mushrooming of the movement and growth of technology, consciously or unconsciously have brought their own impact on the shift in human behavior. Both the positive and negative sides. Understanding the concept of moral values according to Aristotle, was a call at the same time moral teachings for us, especially for the actors, as well as users of technology. So that we as individuals take advantage of the technology have an attitude of readiness, understanding and make him more human. The research, by promoting descriptive qualitative research methods, attempts to provide an overview of the concrete situation of the life of the perpetrators of technology users. Data obtained based on the facts in interviews and presented systematically. The orientation of the paper, that we realize in earnest to implement and apply the cultivation of religious values and ethics in our lives. Character building education at the same time for all users of the technology, needed proclaimed and scheduled as an educational curriculum, both formal and informal. A program of continuous work. With the main objective, enhance the dignity of human life, as well as more broadly as the promotion of human life to the nation. Keywords: moral attitude, Consumer, Roles, Applications, Technologies